The Effects of Same- and Other-Race Facial Expressions of Pain on Temporal Perception - Huang, Shunhang; Qiu, Junjie; Liu, Peiduo; Li, Qingqing; Huang, Xiting (Frontiers in Psychology, 2018)
Previous studies suggested that threatening stimuli lengthen subjective duration, while facial expressions of pain were found to produce a shortening effect on temporal perception in a recent study. Moreover, individuals’ responses to others’ pain were influenced by the individuals’ relationship to a racial group. However, the effects of same- and other-race pained facial expressions on temporal perception, remain unknown. The aim of this present study was to identify the effect expressions of pain have on temporal perception and to explore whether this effect was modulated by the relationship to a racial group. In a temporal bisection task, Chinese participants were presented with pain or neutral facial expressions displayed by Caucasian (other-race) or Chinese (same-race) models in a 400–1600 ms or 200–800 ms condition. Expressions of pain were rated as more arousing, negative and disagreeable, than neutral facial expressions. These scores were not significantly different between same- and other-race facial expressions. Based on the results of the temporal bisection task, both same- and other-race pained facial expressions lengthened the perceived duration in the 400–1600 ms condition, but only same-race pained facial expressions produced this effect in the 200–800 ms condition. We postulate that the existence of a short-lived effect of pained facial expressions on lengthening temporal perception caused by arousal and attention, occurs at an earlier time point for same-race pained facial expressions than for other-race pained facial expressions.